Implementation of Lean Healthcare to improve customer care in a dental center- Cajamarca 2023 - Bardales Chuquilin, Anita Maria Tesoro; Gonzales Abanto, Wilson Alcides; Quispe Vasquez, Luis Roberto (LACCEI, 2024)
The main objective of this research was to implement the Lean Healthcare methodology to improve customer care in a dental center - Cajamarca 2023. The 5 S Methodology tools, Preventive Maintenance Plan and MRP were used to address the problems that the company presented. The population was made up of all the clients of the dental center served in the period from January to July 2023, totaling 840. When implementing this methodology, improvements were observed in customer service time, which influenced satisfaction with the service received. An average customer waiting time of 19 minutes was obtained compared to the 47 minutes that existed before the implementation of the tools and the gap that exists between the average of total perceptions and the average of expectation, the result was 1.3, this being positive for the dental center.